JHEA, Volume 9, n°1 & 2, 2011 - Full Issue - Journal System, (Journal of Higher Education in Africa, 2011)
Contents Introduction Academic Freedom in Africa: Between Local Powers and International Donors Hocine Khelfaoui & Ibrahim Oanda Ogachi ......................... v Libertés académique en Afrique : entre pouvoirs locaux et bailleurs de fonds internationaux Hocine Khelfaoui & Ibrahim Oanda Ogachi ............................. xv The Challenges of Feminism: Gender, Ethics and Responsible Academic Freedom in African Universities Amina Mama ...................................... 1 Neo-liberalism and the Subversion of Academic Freedom from Within: Money, Corporate Cultures and ‘Captured’ Intellectuals in African Public Universities Ibrahim Oanda Ogachi ................................ 25 Academic Freedom and the Constriction of Democratic Space in Botswana: Reflections from an Academic-cum-Politician in the University Space Taolo Lucas ............................................. 49 Regulatory Bodies, Academic Freedom and Institutional Autonomy in Africa: Issues and Challenges – The Nigerian Example Elijah Adewale Taiwo ............................. 63 Peer Review Mechanisms: The Bottleneck of Academic Freedom Elizabeth Ayalew ......................................... 91 Liberté académique en question : contribution à la problématisation d’une notion à partir du cas estudiantin au Sénégal Abdoulaye Guèye ............................ 113 Libertés académiques, syndicalisme et politique en Côte d’Ivoire Goin Bi Zamblé Théodore .................................. 133 Pursuing Excellence in a ‘World-Class African University’: The Mamdani Affair and the Politics of Global Higher Education Isaac A. Kamola .................................... 147